Evaluating the Role of Digital Financial Services in Enhancing Efficiency and Accessibility of Social Safety Net Programs in Bangladesh - Uddin, Md. Jahir; Seddiky, Md. Assraf; Rayhan, Md. Johir; Balaly, Md. Habibullah (European Scientific Journal, ESJ, 2025)
This study examines traditional and existing distribution channels and scrutinizes the effects of Digital Financial Services (DFSs) on delivering Social Safety Net (SSN) benefits. Researchers conducted a field study in the Sylhet Division, which is one of the largest digital areas in Bangladesh; however, there has been a large digitalization drive in the Sylhet Division, especially with the Sylhet City Corporation at the forefront of a mission towards a digital Sylhet. The researchers collected data from 100 respondents, including students, entrepreneurs, government officials, teachers, SSN beneficiaries, and local representatives, using a simple random sampling technique. To improve the theoretical foundation, this study reviewed secondary published materials such as journal articles, books, book chapters, and conference papers. The survey data were analysed using SPSS software, with illustrations of the variables and characteristics. The study findings revealed that traditional banking channels for distributing SSN benefits were ineffective owing to higher costs, mismanagement, corruption, and complexity. Hence, the digital means of financial benefits to the beneficiaries of SSNs function well with the complement of faster service, cost-effectiveness, and efficiency. However, privacy threats, lack of technical knowledge, and risk management issues are prime concerns for the effective operation of DFS to accelerate the benefits of SSNs. The study findings will help researchers, policymakers, and beneficiaries, as well as overcome the existing challenges of DFS in effectively providing SSN benefits.